Coordination chemistry of the [Pt2(μ-S)2 (PPh3)4] metalloligand with π-hydrocarbon derivatives of d6 ruthenium(II), osmium(II), rhodium(III) and iridium(III) - Audi Fong, S.-W. (2014)
10.1016/S0022-328X(03)00464-9